Coping Strategy: A Study on Professional Quality of Life (ProQOL) Among Special Education Teachers - Rismawati, Rismawati; Hidayat, Novi; Estu, Bekti; Ardina, Khoirunnisa; Givency, Samuel (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Professional quality of life (ProQOL) is a critical indicator of psychological well-being among special education teachers, particularly given the emotional and instructional demands of teaching students with special needs. Coping strategies represent an important mechanism for managing occupational stress; however, empirical evidence examining how distinct coping strategies relate to multiple dimensions of ProQOL among special education teachers—especially in non-Western educational contexts—remains limited. To address this gap, this study aimed to examine the differential effects of problem-focused, emotion-focused, and avoidant coping strategies on compassion satisfaction, burnout, and secondary traumatic stress among Indonesian special education teachers. This study employed a quantitative, cross-sectional design with 147 teachers working in special schools in the Bekasi area. Coping strategies were assessed using the 28-item Brief COPE Inventory, while professional quality of life was measured using the 30-item Professional Quality of Life Scale (ProQOL-5). Confirmatory factor analysis was conducted to establish construct validity, and multivariate regression analysis using Mplus 7 was performed to test the proposed relationships. The results indicated that problem-focused and emotion-focused coping were positively associated with compassion satisfaction and negatively associated with burnout, whereas avoidant coping was positively associated with secondary traumatic stress. These findings demonstrate that coping strategies exert differentiated effects across ProQOL dimensions rather than uniform influences, highlighting the importance of adaptive coping in sustaining teachers’ professional well-being. By extending ProQOL research beyond healthcare professions and situating it within the context of special education in Indonesia, this study offers context-specific empirical evidence that may inform targeted interventions aimed at enhancing compassion satisfaction and reducing burnout and trauma-related stress among special education teachers.